NEED OF PRESCRIBING STANDARDS IN AYURVEDA - Krishnan, Remya (International Journal of Ayurveda and Pharma Research, 2015)
Therapeutic prescribing is an art based on science. The art of medical prescribing demands great background knowledge of Basic science of human being for a physician and also a unique skill to blend the Basic science with the specific clinical situation that he intervenes. There is no doubt that the chief essence of good prescribing is to decide the most appropriate therapy which is befitting to the clinical situation in any particular patient. Ayurveda is indepth Basic Science Based -Evidence Based Medicine (BSB-EBM) and not merely Evidence Integrated Medicine (EIM). Any disease by a common name can be caused by multiple variable aetiologies in a subject and also the same aetiology can result in multiple variable pathological effects in different subjects. The main objective of prescribing in Ayurveda is to reverse the cause and circumstances of pathogenesis back to cause and circumstances of health, only by which the cure of a disease is made possible. Cure in Ayurveda refers to Sukha or Arogya (health). A person cured of a disease does no way experience the working of his body and possess great enthusiasm to lead his life.